Internationalization of companies in emerging countries and investment in the research center - Vieira, Dalila Gonçalves (2020)
Discussions on the theme Internationalization of companies have been relevant since the early 1990s. Thus, in view of the fact that the internationalization of companies is a phenomenon with significant expansion since then in a globalized scenario, this article aims to contribute to update the debate on the subject. Structuring the following issues: (1) globalization, (2) the new world economic order, (3) the link between foreign trade and (4) foreign direct investment, as well as, and (5) internationalization as a competitive strategy for strengthening companies in emerging countries through the development of research centers. The methodology used was exploratory and descriptive. As a result of this work, 4 hypotheses are presented and suggested as future studies: That the growth and development of international trade does not boost internationalization in an isonomic way, that emerging countries are the main attractors of international investment, that there is a need to predict the risks present in the internationalization of companies, and finally, that a current and competitive strategy would be the installation of Research Centers in emerging countries that favor the internationalization of companies.